2005
DOI: 10.1080/08039480500360690
|View full text |Cite
|
Sign up to set email alerts
|

Callous–unemotional traits are associated with clinical severity in referred boys with conduct problems

Abstract: Clinical practice with the heterogeneous group of children that present with conduct problems may benefit from improved formats for diagnostic subtyping. We investigated whether high levels of callous-unemotional traits (i.e. lack of empathy, remorselessness and shallow affects) would differentiate clinic-referred conduct-problem boys from those low on such traits. A consecutive series of 41 boys with conduct problems (6-13 years, mean age=9.60 years) referred to public child psychiatric units in Sweden were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 123 publications
(142 reference statements)
5
43
1
Order By: Relevance
“…In this study, we found that CU traits were positively associated with psychosocial impairments. These findings are consistent with recent research that has suggested that CU traits are independently and longitudinally associated with psychiatric problems in the community (10) and clinical severity (9). Together, these results suggest that CU traits are associated with considerable psychiatric treatment needs.…”
Section: Construct Validitysupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, we found that CU traits were positively associated with psychosocial impairments. These findings are consistent with recent research that has suggested that CU traits are independently and longitudinally associated with psychiatric problems in the community (10) and clinical severity (9). Together, these results suggest that CU traits are associated with considerable psychiatric treatment needs.…”
Section: Construct Validitysupporting
confidence: 82%
“…Together, these results suggest that CU traits are associated with considerable psychiatric treatment needs. Moreover, CU traits were significantly associated with social problems, and this is consistent with previous research (9,60,61).…”
Section: Construct Validitysupporting
confidence: 81%
See 1 more Smart Citation
“…However, much of this research has focused on CU traits and their association with antisocial behavior in general, for which aggression is just one component. That is, in terms of their association specifically with aggression, CU traits seem to designate a subgroup of antisocial youth who show more severe aggression and who are more likely to show both instrumental (e.g., for gain) and reactive (e.g., in response to perceived provocation) aggression (Enebrink et al, 2005;Fanti et al, 2009;Fite et al, 2009;Kruh, Frick, & Clements, 2005). For example, in a sample of incarcerated juvenile offenders (ages 16 to 21), Kruh et al (2005) identified two subtypes of violent offenders.…”
Section: Callous-unemotional Traits and Aggressionmentioning
confidence: 99%
“…Although these studies were weighted toward adolescent samples and tended to have limited follow-up periods (e.g., 1 to 2 years), the review did include studies with samples as young as age 3 and with follow-up periods as long as 10 years (Gretton, Hare, & Catchpole, 2004). Not included in this review were 12 additional concurrent studies with clinical, forensic, and community samples showing the association between CU traits and severity of conduct problems (Dadds, Whiting, & Hawes, 2006), violence and aggression (Barry et al, 2007;Dolan & Rennie, 2006a;Enebrink, Anderson, & Langstrom, 2005;Fite, Stoppelbein, & Greening, 2009;Skeem & Cauffman, 2003;Vitacco, Neumann, Caldwell, Leistico, & Van Rybroek, 2006), bullying (Fanti, Frick, & Georgiou, 2009;Muñoz, Qualter, & Padgett, 2010;Viding, Simmonds, Petrides, & Frederickson, 2009), and delinquency (Dolan & Rennie, 2006b;Loeber et al, 2005;Poythress, Dembo, Wareham, & Greenbaum, 2006). Also, four longitudinal studies show the predictive relationships between CU traits and later antisocial personality (Loeber, Burke, & Lahey, 2002), violence and aggression (Ridenour, Marchant, & Dean, 2001), and delinquency (Lynam et al, 2009;Pardini, Obradovic, & Loeber, 2006).…”
Section: Callous-unemotional Traits and Aggressionmentioning
confidence: 99%